2008
DOI: 10.1086/593352
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of AGN Feedback in Galaxy Clusters and Groups: Impact on Gas Fractions and the L X - T Scaling Relation

Abstract: Recently, rapid observational and theoretical progress has established that black holes (BHs) play a decisive role in the formation and evolution of individual galaxies as well as galaxy groups and clusters. In particular, there is compelling evidence that BHs vigorously interact with their surroundings in the central regions of galaxy clusters, indicating that any realistic model of cluster formation needs to account for these processes. This is also suggested by the failure of previous generations of hydrody… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

45
274
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(321 citation statements)
references
References 34 publications
45
274
2
Order By: Relevance
“…Sijacki & Springel (2006) developed a model for AGN heating via hot thermal bubbles in a cosmological simulation of cluster formation. Puchwein et al (2008) have shown that the observed L X − T relation is successfully reproduced without invoking excessive cooling in the central region of the simulated clusters. However this model does fail to reproduce the observed entropy profiles.…”
Section: Interpretation Of Scaling Relations With Simulationsmentioning
confidence: 79%
“…Sijacki & Springel (2006) developed a model for AGN heating via hot thermal bubbles in a cosmological simulation of cluster formation. Puchwein et al (2008) have shown that the observed L X − T relation is successfully reproduced without invoking excessive cooling in the central region of the simulated clusters. However this model does fail to reproduce the observed entropy profiles.…”
Section: Interpretation Of Scaling Relations With Simulationsmentioning
confidence: 79%
“…Most state-of-the-art cosmological zoom-in simulations of galaxy clusters reach a spatial resolution of "kpc (Puchwein et al 2008;Teyssier et al 2011;Ettori et al 2012;Martizzi et al 2014b;Le Brun et al 2014;Lau et al 2015;Sembolini et al 2015). Such simulations are challenging since they require a very large dynamic range of scales to be captured: from the scales at which galaxies assemble their stars to the scale at which cosmological gas accretion onto clusters happens.…”
Section: Introductionmentioning
confidence: 99%
“…Several works, based on both observations and simulations, have indicated that the L X −T vir relation in low-mass halos with a central radio source differs systematically from that in systems without a central radio source Croston et al 2005;Puchwein et al 2008). Studies also show that clusters with strong cooling, as indicated by either the short cooling times of the intracluster gas or high classical gas mass deposition rates, lie on a different L X −T vir plane (e.g., Allen & Fabian 1998;O'Hara et al 2006).…”
Section: Introductionmentioning
confidence: 99%